The characteristics of real and pseudo-true thinking in STEM students' analytical thinking process in solving set problems - Agus Maqruf; Tatang Herman (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
It is essential to analyze students' cognitive development, particularly in mathematics, to determine their ability to solve problems effectively. This research focuses on analytical thinking as a critical component of students' problem-solving processes in mathematics. The subjects of this study were two students from a school in Bandung who are part of a STEM program, which incorporates additional learning approaches in science, technology, engineering, and mathematics. Through this approach, researchers aim to understand the students' analytical thinking processes and characteristics in solving given problems using qualitative methods. The instruments utilized in this study were tests and interview guidelines. The findings revealed that each student exhibited two distinct analytical thinking characteristics. The "real true thinking" character is where students can provide justification for their correct problem-solving results and navigate through the entire analytical thinking process. In contrast, the pseudo-true thinking character is unable to justify correct problem-solving and fails to complete the analytical thinking process, particularly at the differentiation stage.